Expression of H2S in Gestational Diabetes Mellitus and Correlation Analysis with Inflammatory Markers IL-6 and TNF-α - Yucui Teng; Shuxia Xuan; Ming Jiang; Li Tian; Jinjing Tian; Qian Chang (Journal of Diabetes Research)
Background. Gestational diabetes mellitus (GDM) is a severe threat to the health of both mother and child. The pathogenesis of GDM remains unclear, although much research has found that the levels of hydrogen sulfide (H2S) play an important role in complications of pregnancy. Methods. We collected venous blood samples from parturient women and umbilical vein blood (UVB) and peripheral venous blood (PVB) samples one hour after childbirth in the control, GDM-, and GDM+ groups in order to determine the concentration of glucose and H2S in plasma; to measure levels of TNF-α, IL-1β, IL-6, TGF-β1, and ADP in parturient women and the UVB of newborns; and to find the correlation of H2S with regression. Results. We found that, with the elevation of glucose, the level of H2S was decreased in GDM pregnant women and newborns and the concentrations of IL-6 and TNF-α were upregulated. With regression, IL-6 and TNF-α concentrations were positively correlated with the level of blood glucose and negatively correlated with H2S concentration. Conclusion. This study shows that downregulation of H2S participates in the pathogenesis of GDM and is of great significance in understanding the difference of H2S between normal and GDM pregnant women and newborns. This study suggests that IL-6 and TNF-α are correlated with gestational diabetes mellitus. The current study expands the knowledge base regarding H2S and provides new avenues for exploring further the pathogenesis of GDM.